2012
DOI: 10.1155/2012/571516
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life in Iranian Patients with Acne

Abstract: Acne is a chronic inflammatory disease of pilosebaceous units. Although the acne isnot a life threatening disease, studies have revealed that it has significant effect on self-image and quality of life. The purpose of this paper was to investigate the health-related quality of life in patients with acne in an Iranian context. Dermatology Life Quality Index (DLQI) and Cardiff Acne Disability Index (CADI) were used for measuring quality of life, and severity of acne was measured by Global Acne Grading System (GA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
23
2
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 16 publications
10
23
2
3
Order By: Relevance
“…The mean DLQI and CADI scores in our study were similar to previous studies [10,[14][15][16][17][18]. However, the studies performed on students at their school, reported lower DLQI and CADI scores [19,20].…”
Section: Discussionsupporting
confidence: 90%
“…The mean DLQI and CADI scores in our study were similar to previous studies [10,[14][15][16][17][18]. However, the studies performed on students at their school, reported lower DLQI and CADI scores [19,20].…”
Section: Discussionsupporting
confidence: 90%
“…26,27 In present study it was observed that there was a moderate to very large effect on 67.7 % based on DLQI scores similar to study by Safizedeh H et al who found that there was a moderate to very large influence on quality of life in 51.8% of patients Haritha et al also found moderate to very large effect in 64.18% of patients. 28,29 In present study it was observed that there was medium to high effect on 68.7% of patients based on CADI scores which indicates high psychosocial burden from acne. Similarly hanisha et al reported that based on specific responses of CADI 71.1% of the patients felt aggressive, frustrated or embrassed as a result of having acne.…”
Section: Resultsmentioning
confidence: 48%
“…H.Safizadeh et al found that acne influenced the quality of life in 51.8% of the patients based on DLQI score. 25 and Hanisha et al reported that based on the specific responses of CADI, 71.1% of the patients felt aggressive, frustrated or embarrassed as a result of having acne 26 .Studies have shown that impairment of Quality of Life in females was more when compared to males which could be due to the fact that adolescent girls are more vulnerable to the negative psychological effects of acne 27,28,29 .The Quality of Life may also be affected by the severity of acne. Krejci Manwaring et al reported a positive correlation between acne severity and poorer quality of life.…”
Section: Discussionmentioning
confidence: 99%